Between the devil and the deep blue sea : the role of the Amundsen Sea continental shelf in exchanges between ocean and ice shelves - Heywood, Karen; Biddle, Louise; Boehme, Lars; Dutrieux, Pierre; Fedak, Michael Andre; Jenkins, Adrian; Jones, Richard W.; Kaiser, Jan; Mallett, Helen; Naveira Garabato, Alberto C.; Renfrew, Ian A.; Stevens, David P.; et al. (Oceanography, 2016)
This work was supported by funding from the UK Natural Environment Research Council's iSTAR Program through grants NE/J005703, NE/J005649/1 and NE/J005770/1. The Amundsen Sea is a key region of Antarctica where ocean, atmosphere, sea ice and ice sheet interact. For much of Antarctica, the relatively warm ocean water in the open Southern Ocean (a few degrees above freezing) is unable to reach the continental shelf in large volumes under current climate conditions. In the Amundsen Sea, however, warm water penetrates onto the continental shelf and provides heat that can melt the underside of the floating ice shelves. Here we discuss how the role of the ocean has come under increased scrutiny in recent years, because ocean heat fluxes have been implicated in the thinning of the ice shelves. We present observations from the Amundsen Sea in 2014 and discuss their implications, highlighting aspects where our understanding is still incomplete. Peer reviewed